Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/2515-7647/ab7d82
|View full text |Cite
|
Sign up to set email alerts
|

Sub-cycle temporal evolution of light-induced electron dynamics in hexagonal 2D materials

Abstract: Two-dimensional materials with hexagonal symmetry such as graphene and transition metal dichalcogenides are unique materials to study light-field-controlled electron dynamics inside of a solid. Around the K-point, the dispersion relation represents an ideal system to study intricately coupled intraband motion and interband (Landau-Zener) transitions driven by the optical field of phase-controlled few-cycle laser pulses. Based on the coupled nature of the intraband and interband processes, we have recently obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…We move on to graphene, which is a hexagonal Dirac semi-metal with band touching at the K and K' points. Previous theoretical and experimental work showed that one can generate strongly-driven photocurrents in graphene with monochromatic few-cycle laser pulses [33][34][35][36]. Figure S6 explores current injection from the co-rotating ω-2ω field, showing that similar effects occur in the long-pulse regime (the field is polarized within the graphene sheet).…”
Section: Additional Results In Other Systemsmentioning
confidence: 79%
See 2 more Smart Citations
“…We move on to graphene, which is a hexagonal Dirac semi-metal with band touching at the K and K' points. Previous theoretical and experimental work showed that one can generate strongly-driven photocurrents in graphene with monochromatic few-cycle laser pulses [33][34][35][36]. Figure S6 explores current injection from the co-rotating ω-2ω field, showing that similar effects occur in the long-pulse regime (the field is polarized within the graphene sheet).…”
Section: Additional Results In Other Systemsmentioning
confidence: 79%
“…Here the photon energies are resonant with 2 nd -and 3 rdorder perturbative transitions that interfere, and the inversion symmetry is effectively broken by the twocolor field (making the effect highly sensitive to the two-color relative phase). The resonant and perturbative nature of these effects precludes access to ultrafast dynamics and possible applications in the Terahertz regime, and is also limited in its conversion efficiency [29].More recently, nonlinear photocurrents were predicted and observed in dielectrics [30][31][32] and graphene [33][34][35][36] driven by intense quasi-monochromatic few-cycle pulses. The mechanism creating these photocurrents relies on the vector potential of the light field to have a nonzero time integral [32], i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If the light becomes circularly polarized, the intraoptical-cycle LZSM interference cannot occur and there is no respective change in the current. The intermediate situation takes place for laser pulses with various degrees of ellipticity (Boolakee et al, 2020;Heide et al, 2020Heide et al, , 2019Heide et al, , 2018.…”
Section: Graphenementioning
confidence: 99%
“…Also, the idea of ω − 2ω bi-circular fields driven HHG is extended from atomic systems [26,27] to solids [28]. Moreover, remarkable works were reported on electron dynamics in graphene via intense laser pulse [29][30][31][32], including Floquet-engineered valleytronics [33,34].…”
Section: Introductionmentioning
confidence: 99%